Chemical composition and bioactive compounds of Riceberry rice produced under organic and conventional practices - Kunnam, J.; Teamkao, P.; Aninbon, C. (My University, 2023)
It is often stated that organic rice has a higher content of healthy phytochemicals than ordinary rice, and the facts on this claim obtained experimentally are rare. Riceberry is a new rice variety in Thailand. This study aimed to evaluate the effects of organic practice and conventional practice on the content of chemical composition and bioactive compounds in Riceberry rice. The results showed that agricultural practices were not significantly different for grain yield in the first year, but they were different in the second year. Rice produced by organic practice had a higher content of iron, gamma-aminobutyric acid, total phenolic and anthocyanin (4.15, 1.67, 41.3 and 20.1 mg/100 g dry weight in the first year, and 4.06, 3.37, 89.7 and 14.7 mg/100 g dry weight in the second year) than that produced by conventional practice (2.25, 1.11, 38.8 and 6.89 mg/100 g dry in the first year, and 1.96, 2.77, 54.1 and 5.71 mg/100 g dry in the second year). Rice produced by organic practice also had lower sugar content (2.92 g/100 g dry weight in the first year, and 1.99 g/100 g dry weight in the second year) than that produced by conventional practice (3.46 g/100 g dry weight in the first year, and 2.81 g/100 g dry weight in the second year). Gamma oryzanol and antioxidant capacity were also lower in organic rice compared to conventional rice. This study indicated that organic Riceberry rice had a higher quality compared to non-organic rice.
Keywords: Anthocyanin; cereal; fertilizer; minerals; polyphenols